2011
DOI: 10.3892/ol.2011.396
|View full text |Cite
|
Sign up to set email alerts
|

IGF-IR in patients with advanced colorectal cancer in correlation with certain clinico-morphological factors: Initial report

Abstract: Abstract. The insulin-like growth factor (IGF) system comprises two types of peptides (IGF-I and IGF-II), two types of receptors (IGF-IR and IGF-IIR) and six IGF-binding proteins (BP). This system is mainly responsible for the growth and division of cells in the body, regulation of the cell cycle and prevention of apoptosis. The expression of IGF-IR was assessed in the cells of resected primary colorectal tumours in 88 patients (age, 36-87 years; mean 64.78; males, 48 and females, 40) treated surgically at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Our study is not unique in finding lower expression levels at advanced tumor stages: in breast and colorectal cancer this phenomenon has also been described [19,26,27]. Also, the decrease in expression might be due to the dedifferentiation process to which cancer cells are exposed; by becoming more invasive the expression of the IGF-1R gets lost [27].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our study is not unique in finding lower expression levels at advanced tumor stages: in breast and colorectal cancer this phenomenon has also been described [19,26,27]. Also, the decrease in expression might be due to the dedifferentiation process to which cancer cells are exposed; by becoming more invasive the expression of the IGF-1R gets lost [27].…”
Section: Discussionsupporting
confidence: 69%
“…A pathologist specialized on GI pathology (KBI) scored the immunohistochemically stained slides, blinded from the clinical data. Thereby, the staining was scored as “absent or low expression” or “high expression.” “High expression” was defined as intense staining in at least 10% of the cells of interest (dysplastic or carcinoma cells), as used in an earlier study on IGF‐1R expression . Membranous or cytoplasmatic localization of the IGF‐1R was also scored.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is furthermore reflected in the lower levels of these IGF pathway proteins and their mRNAs in association with shorter 10-year disease-free survival and overall rates. A decrease in both IGF1R protein and gene expression levels has been described before in esophageal adenocarcinoma, colorectal and breast cancer (Schnarr et al 2000, Allison et al 2007, Kuklinski et al 2011, De Bruijn et al 2015 and might reflect a dedifferentiation process. Indeed, two recent genomic studies have identified distinctive m(i) RNA expression profiles, separating PanNET with liver metastases (metastasis like primary tumor subtype) from well-differentiated PanNETs (well-differentiated islet/insulinoma tumor subtype), further underscoring dedifferentiation to be reflected in gene expression signatures (Sadanandam et al 2015, Scarpa et al 2017.…”
Section: Discussionsupporting
confidence: 54%
“…At present, tissue sampling remains the gold standard in the assessment of tumour genetic features [17]. A fraction of CRC DNA is shed into the blood, and sensitive methods to detect it have now been introduced.…”
Section: Nucleic Acidsmentioning
confidence: 99%